Design and Development of a Polyherbal Formulation for the Control of Insulin Resistance in Type 2 Diabetes - Masoodali Kazi, Sarfaraz; Pore, Amol Vilas; Kamble, Suraj Udhavrao; Dongare, Gopika Dattatray; Bais, Sanjay Kisanrao (Journal of Neonatal Surgery, 2025)
Type 2 diabetes mellitus is a chronic metabolic disorder characterized by impaired insulin sensitivity and persistent hyperglycemia, leading to severe long-term complications affecting cardiovascular, renal, and neurological systems. The growing global prevalence of Type 2 Diabetes Mellitus has increased the demand for safe and effective therapeutic strategies to control insulin resistance and maintain glucose homeostasis. Conventional pharmacological treatments are effective but are often associated with adverse effects and long-term dependency, which has encouraged the exploration of plant-based therapeutic alternatives. This study focuses on the design and development of a polyherbal formulation composed of selected medicinal plant extracts known for their antihyperglycemic, antioxidant, and insulin-sensitizing properties. The formulation integrates multiple bioactive phytoconstituents that act synergistically to enhance insulin receptor sensitivity, regulate glucose metabolism, and improve pancreatic β-cell function. The polyherbal combination is developed through systematic selection, extraction, formulation optimization, and preliminary pharmacological evaluation to ensure efficacy and stability. Experimental evaluation of the formulation demonstrates its potential to reduce insulin resistance, improve glucose uptake in peripheral tissues, and regulate blood glucose levels. The synergistic action of phytochemicals such as flavonoids, alkaloids, and polyphenols contributes to improved metabolic regulation and reduction of oxidative stress associated with Type 2 Diabetes Mellitus. The results indicate that the developed polyherbal formulation may serve as a promising natural therapeutic approach for the management of insulin resistance and glycemic control, offering a safer and complementary alternative to conventional antidiabetic therapies..